Book Review: A. Kanafani and K. Kuroda (eds.) Global Competition in Transportation Markets: Analysis and Policy Making - Nijkamp, Peter (European Journal of Transport and Infrastructure Research, 2006)
I have read the above book on a long flight to Japan. And it was certainly not boring literature; it kept me awake during a twelve hour flight. This is certainly the type of book that one likes to see in the hands of researchers and students. It contains 16 individual and selfcontained chapters of a high quality. They all center around the theme of competition and globalization in modern transportation markets. The book, an edited volume based on proceedings of a conference, comprises essentially two disjoint parts, the first one dealing with air transport and the second one with maritime transport. Clearly, these are rather different markets and one may wonder what these markets have in common. The editors offer only a two-page preface in which they try to indicate that these markets may have indirectly some commonalities. These markets share the following features. They are both globally and locally subjected to strict competition. Next, both markets are characterized by economies of scale (including economies of scope and density in networks). Furthermore, both markets exhibit clearly the features of network externalities at various geographical networks. And finally, these markets display a high degree of dynamics and much uncertainty, so that the design of proper policies is not an easy task. A more profound editorial synthesis connecting both markets from a fundamental globaleconomic perspective would certainly have been desirable. This is perhaps the only weakness in this book.